2006
DOI: 10.1021/ma061033n
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Threading α-Cyclodextrin onto Cationic and Zwitterionic Poly(bola-amphiphiles)

Abstract: The amphiphilic polymers, poly(iminoundecamethylene), poly((N-methylimino)undecamethylene), poly((N,N-dimethylammonio)undecamethylene), and poly((N-methylimino)undecamethylene-N-oxide) were synthesized from nylon-11 by BH 3 reduction of amide groups to amino groups and subsequent methylations. The poly(N-oxide) was obtained by H 2 O 2 oxidation of the polymeric tertiary amine. Since the polymers and their inclusion compounds were water-soluble, threading kinetics of R-cyclodextrin rings onto these polymers cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 48 publications
(101 reference statements)
1
29
0
Order By: Relevance
“…This is consistent with the poly(ε‐lysine)/α‐CD system, in which the yield of PPRX is not altered with the ionic strength of the solution . Additionally, it is known that the polymers bearing long alkyl chains along the main chain are favorable for PPRX formation, due to the hydrophobic interaction between alkyl chains and inner cavity of CDs, which stabilizes the inclusion complex . For example, Wenz et al have found that α‐CD can threaded onto the polymers even though bearing quaternary ammonium salt or zwitterionic groups along polymer main chain .…”
Section: Resultssupporting
confidence: 72%
“…This is consistent with the poly(ε‐lysine)/α‐CD system, in which the yield of PPRX is not altered with the ionic strength of the solution . Additionally, it is known that the polymers bearing long alkyl chains along the main chain are favorable for PPRX formation, due to the hydrophobic interaction between alkyl chains and inner cavity of CDs, which stabilizes the inclusion complex . For example, Wenz et al have found that α‐CD can threaded onto the polymers even though bearing quaternary ammonium salt or zwitterionic groups along polymer main chain .…”
Section: Resultssupporting
confidence: 72%
“…Steric hindrance and the hydrophilicity of the cationic groups stabilize the polypseudorotaxanes between the polyelectrolyte and α-CD. [29] …”
Section: Formation Of Inclusion Complexes Of Cds With Polymersmentioning
confidence: 99%
“…Ionenes are only slowly complexed by CD at elevated temperatures (70°C), due to steric hindrance from the bulky dimethylammonium groups. At lower temperatures, 25-37°C, they are stable for a limited period of time in aqueous solution (1 -10 days) [27,28]. Not only native CDs but also cationic CD derivatives can be threaded onto ionenes.…”
Section: Introductionmentioning
confidence: 99%